Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Haus! Bandung, Indonesia - Sadewa, Akbar Maulana (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study was to determine the influence of brand ambassadors on Haus! Bandung. This study used a descriptive survey method by distributing questionnaires via g-form to 110 respondents who had purchased Haus! Bandung. Data processing was carried out using the normality test method, linearity test and simple linear regression analysis. From this processing, the results show that brand ambassadors have a positive and significant influence of 16.7% on purchasing decisions at Haus! Bandung. This value is obtained by looking at the R Square column or the coefficient of determination in the table of simple linear regression analysis results. In addition, there is a weak correlation between the two variables, with a correlation coefficient of 0.409. This value indicates the relationship between brand ambassadors and purchasing decisions is included in the weak category because it is in the range of 0.21-0.40.